Efficiency of municipal legislative chambers - Alexandre Manoel Angelo da Silva; Roberta da Silva Vieira; Angelo José Mont'alverne Duarte (EconomiA, 2015)
A novel study of Brazilian city council efficiency using the non-parametric estimator FDH (free disposal hull) with bias correction is presented. In regional terms, study results show a concentration of efficient councils in the southern region. In turn, those in the northeastern and southeastern regions are among the most ineffective councils. In these latter two regions, most councils could at least double their outputs while maintaining the same volume of inputs. Regarding population size, for cities with up to 500,000 inhabitants, more than 60% of city councils could at least quadruple their output. Regarding inefficiencies revealed through non-discretionary variables (environmental variables), the study results show a correlation between councilor education levels and city council efficiency. – – Neste artigo, analisa-se pioneiramente a eficiência das câmaras legislativas municipais brasileiras, a partir do estimador n\~ao paramétrico FDH (Free Disposal Hull), com a respectiva correç\~ao de seu viés. Em termos regionais, os resultados obtidos mostram grande concentraç\~ao de câmaras eficientes na regi\~ao Sul. Por sua vez, dentre as câmaras ineficientes, destacam-se as das regi\~oes Nordeste e Sudeste. De fato, nestas duas regi\~oes, a maioria das câmaras poderia ao menos duplicar a produç\~ao mantendo o mesmo nível de insumos. Do ponto de vista populacional, nas cidades com até 500.000 habitantes o percentual de câmaras municipais que podem pelo menos quadruplicar seu produto é maior do que 60%. Em relaç\~ao à explicaç\~ao das ineficiências por meio de variáveis n\~ao discricionárias (variáveis ambientais), indica-se que quanto maior for o grau de escolaridade média dos vereadores, maior é a eficiência da câmara legislativa onde atuam.
Keywords: C10; C14; H70; 330; Efficiency; City councils; FDH